Married women's autonomy in modern contraceptive utilization in Kutaber district, Northeast Ethiopia. - Getachew Amanu Bogale; Mastewal Arefaynie Temesgen; Kemal Ahmed Seid; Bantalem Amanu Bogale (PLOS Global Public Health)
Married women's decision-making autonomy in modern contraceptive utilization is extremely important for better maternal and child health outcomes. Most studies in Ethiopia have not incorporated women's freedom of movement and control over finance when assessing married women's autonomy in modern contraceptive utilization. Previously conducted studies measured women's autonomy using different variables. This study aimed to measure married women's autonomy in contraceptive use in Kutaber district using better outcome measuring tool. A community-based cross-sectional study was conducted from July 10 to August 13, 2024. Interviews were conducted with 420 married women selected via a simple random sampling technique from the study population. Bivariable logistic regression was performed, and variables with p-values < 0.25 were included in the multivariable logistic regression, with a p-value < 0.05 considered statistically significant. Four hundred and eight (408) married women participated, resulting a response rate of 97%. About two-thirds (63.5%, 95% CI (58.3%-68.4%)) of the married women had autonomy in modern contraceptive utilization. Having household decision-making power (Adjusted Odd Ratio (AOR: 6.59, 95% Confidence Interval (CI (3.82,11.36))), being ≥18 years old at first marriage (AOR: 2.65, 95% CI (1.45,4.86)), having 3-4 live children (AOR: 3.74, 95% CI (1.82,7.67)), having ≥ 5 children (AOR: 10.78, 95% CI (3.60,32.31)), attending secondary school (AOR: 3.15, 95% CI (1.38,7.19)), and being in a marital union for 5-10 years (AOR: 2.90, 95% CI (1.20,6.98)) were significantly associated with married women's autonomy in modern contraceptive utilization. The prevalence of married women's autonomy in modern contraceptive utilization was high. Tackling early marriage and empowering women through adult education programs are recommended to improve married women's autonomy.